1981
DOI: 10.1295/polymj.13.273
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation and Viscoelastic Behavior of Semicompatible Polymer Blends: Poly(vinylidene fluoride)/Poly(methyl methacrylate) System

Abstract: ABSTRACT:Thermal and dynamic mechanical analyses of variously processed blends of poly(vinylidene fluoride) (PVF2) and poly(methyl methacrylate) (PMMA) were carried out to elucidate the effects of lower-critical-solution-temperature (LCST) behavior reported earlier by Paul on the morphologies and properties of this system. The two components are miscible in the blends with PVF2 content 4>w < 0.6. Such blends exhibit single glass transition at T;s, which follow the Gordon-Taylor scheme. On the other hand, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 14 publications
4
43
0
Order By: Relevance
“…Recently, Martines-Salazar et al [13][14] have reported that the glass transition temperature-composition relationship for the completely amorphous PVDF/PMMA blends could be fitted by the Gordon-Taylor equation [16]. This result is in accord with previous observations by Hirata and Kotaka [6], at least until the PVDF content does not exceed 60wt%. Indeed, beyond this composition, PVDF starts to crystallize and discrepancy is reported to occur.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…Recently, Martines-Salazar et al [13][14] have reported that the glass transition temperature-composition relationship for the completely amorphous PVDF/PMMA blends could be fitted by the Gordon-Taylor equation [16]. This result is in accord with previous observations by Hirata and Kotaka [6], at least until the PVDF content does not exceed 60wt%. Indeed, beyond this composition, PVDF starts to crystallize and discrepancy is reported to occur.…”
Section: Introductionsupporting
confidence: 84%
“…The transition behaviour of semicrystalline poly(vinyli-dene fluoride) (PVDF) has been extensively studied [1][2][3][4][5][6][7][8][9][10]. In addition to melting, PVDF usually exhibits at least two transitions that have been assigned to the α-transition and the β-transition, respectively, as the temperature is increased.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations